Manifestations, clinical course and prognostic markers in cutaneous polyarteritis nodosa. (4th October 2020) - Munera‐Campos, Mónica; Bielsa, Isabel; Martínez‐Morillo, Melania; Aparicio, Gloria; Olivé, Alejandro; Ferrándiz, Carlos
Summary: Background and objectives: Cutaneous polyarteritis nodosa (CPAN) is a comparatively rare form of vasculitis that affects small arteries and arterioles in the panniculus and dermo‐subcutaneous junction. Limited information is available regarding its course in the European population. The aim of this study is to characterize the manifestations and prognostic markers of recurrence in CPAN. Patients and methods: We report a retrospective study of patients with clinical and histopathologic evidence of CPAN, which was treated at two tertiary referral centers in Spain between 1989 and 2019. Results: 31 patients were included. The most frequent manifestation was subcutaneous nodules (90.3 %); ulcers were frequent at diagnosis (35.5 %). Two thirds of the patients had at least one extracutaneous manifestation. Seventeen patients (54.8 %) experienced relapse. The strongest predictor of recurrence was ulceration in the initial episode (OR 18.6; 95 % CI 2.73–38; p < 0.01). The pre‐treatment results of laboratory parameters associated with inflammation (such as C‐reactive protein and neutrophil‐to‐lymphocyte ratio) were significantly higher in the relapsing group. There were no disease‐related deaths and none of the patients developed systemic PAN. Conclusions: Although CPAN is a vasculitis limited to the skin, symptoms may involve adjacent skeletal muscle or peripheral nerves. While the condition is not life‐threatening, the presence of ulceration and elevation of certain laboratory parameters predicts a worse prognosis.